Multi-responsive chemosensing and photocatalytic properties of three luminescent coordination polymers derived from a bifunctional 1, 1′-di(4-carbonylphenyl)-2, 2′-biimidazoline ligand. Issue 37 (4th September 2020) - Wang, Jun; Chen, Ning-Ning; Qian, Jin; Chen, Xuan-Rong; Zhang, Xin-Yue; Fan, Liming
Abstract : Three 3D Zn II /Cd II CPs were synthesized to act as multiresponsive luminescent sensors for Fe 3+, Cr2 O7 2− and NZF antibiotic. The photocatalytic studies indicate that the CPs 1–3 have good photocatalytic capability in degradation of MB. Abstract : Based on the bifunctional ligand 1, 1′-di(4-carbonylphenyl)-2, 2′-biimidazoline (H2 L), three luminescent coordination polymers, with the formula of {[Cd(L)(H2 O)]·5H2 O} n (1 ), {[Cd4 (L)3 (DMF)Cl2 ]·H2 O} n (2 ), and {[Zn(L)]·H2 O} n (3 ), were designed and characterized. CP 1 is a 3D 4, 4-c {4 2 ·8 4 } pts net, and CP 2 shows an unprecedented 3D 6-nodal (4, 4, 4, 4, 5, 5)-c {4·6 4 ·8}2 {4·6 5 }2 {4 2 ·6 5 ·8 3 }{4 2 ·6 7 ·8} net, while CP 3 is a 3D 4, 4-c {4 2 ·6 2 ·8 2 }{4 2 ·6 3 ·8} sqc5577 net. Benefiting from their excellent chemical stability and luminescence properties, these CPs possess efficient multi-functional fluorescence sensing ability toward Fe III ions, Cr2 O7 2− anions, and NZF antibiotics in aqueous media with high sensitivity and high selectivity. Besides, the mechanisms of luminescence sensing were revealed from the viewpoint of resonance energy transfer (RET) and photoinduced electron transfer (PET). Furthermore, the photocatalytic activities for the degradation of methylene blue (MB) of CPs 1–3 under UV light have been investigated.